Alkalmi munkavállalói könyves foglalkoztatás munkaadói és munkavállalói interjúk tükrében - András Semjén; István János Tóth; Mihály Fazekas (Hungarian Academy of Sciences, Institute of Economics, 2008)
– The study aims at illuminating the following questions: (1) what characterizes enterprises and workers using the temporary work booklet, (2) in what ways do actors on the labour market use the booklet, (3) what motivations drive the economic actors when they decide about the ways of using the booklet, (4) what effects does the temporary work booklet have on hidden employment. Furthermore, we also arrive at some more general conclusions relevant to the general functioning of the Hungarian hidden economy. The empirical material on which our study is based was collected through semi-structured interviews with employers and employees. The interviewees were selected using a "snowballing" technique. Our main results are the following: (1) the temporary work booklet is mostly used for seasonal, temporary employment in accordance with the intentions inherent in the regulation. Nevertheless, (2) in most cases the booklet wasn't used in compliance with the specific rules of the regulation. (3) Decisions whether to evade taxes were mostly influenced by a rational calculation of costs and benefits associated with evasion. (4) The temporary work booklet did decrease to some extent unreported employment, as many unreported workers employed previously gained semi-legal employment status thanks to the booklet. (5) The clarification of some connections between employment using the temporary work booklet and the hidden economy underlined the importance of trust and stable relations between the actors, and it also showed that a significant group of economic actors has norms that do not condemn tax evasion, and only partially approve tax compliance.
Keywords: E24; E26; H26; Z13; 330; hidden economy; policies to reduce the size of the hidden economy; temporary work; emploment with the temporary work booklet; favourable tax treatment of temporary employment; Schattenwirtschaft; Befristete Beschäftigung; Steuervermeidung; Ungarn